2010
DOI: 10.1002/glia.21109
|View full text |Cite
|
Sign up to set email alerts
|

Bid regulates the immunological profile of murine microglia and macrophages

Abstract: Apoptosis is a controlled cell-death process mediated inter alia by proteins of the Bcl-2 family. Some proteins previously shown to promote the apoptotic process were found to have nonapoptotic functions as well. Microglia, the resident immune cells of the central nervous system, respond to brain derangements by becoming activated to contend with the brain damage. Activated microglia can also undergo activation-induced cell death. Previous studies have addressed the role of core apoptotic proteins in the death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…These results are also in 10 agreement with a study showing a non-apoptotic, Bid-dependent activation of COX-II in 11 fibroblasts exposed to alkylating agents (Luo et al, 2010). Recently, it was found that bid-12 deficient macrophages and microglia also exhibited an impaired ability of pro-inflammatory 13 cytokine production (Mayo et al, 2011). It is therefore conceivable that Bid plays a key role 14 in the supply of pro-inflammatory cytokines from both microglia and astroglia (Nagai et al,15 2007), thereby amplifying inflammation (Yamanaka et al, 2008).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…These results are also in 10 agreement with a study showing a non-apoptotic, Bid-dependent activation of COX-II in 11 fibroblasts exposed to alkylating agents (Luo et al, 2010). Recently, it was found that bid-12 deficient macrophages and microglia also exhibited an impaired ability of pro-inflammatory 13 cytokine production (Mayo et al, 2011). It is therefore conceivable that Bid plays a key role 14 in the supply of pro-inflammatory cytokines from both microglia and astroglia (Nagai et al,15 2007), thereby amplifying inflammation (Yamanaka et al, 2008).…”
supporting
confidence: 81%
“…However, in most cell types, this direct activation 19 pathway is not sufficient to activate apoptosis, and an amplification loop is required for cell 20 death execution that involves the BH3-only protein Bid, and hence engages the 21 mitochondrial apoptosis pathway (Lovell et al, 2008;Luo et al, 1998 (Guegan et al, 2002). Interestingly, Bid was recently implicated in the production of pro-25 inflammatory cytokines in macrophages and microglia (Mayo et al, 2011) and was 26 reported to be involved in the activation of the transcription factor nuclear factor-κB (NF-1 κB) in response to stimulation of pattern recognition receptors in intestinal epithelial cells, 2 independent of its direct apoptosis-regulating function (Yeretssian et al, 2011). Therefore, 3 in the present study we sought to clarify the role of Bid in the context of neurodegeneration 4 and neuroinflammation relevant to ALS.…”
mentioning
confidence: 99%
“…Mixed glial cultures were prepared from cerebral cortices of 1‐ to 3‐d‐old C57BL/6 male mice (University of Seville Animal Core Facility), and microglia were isolated by mild trypsinization as previously described (30), with minor modifications as follows. Sixteen mouse brains were used per culture batch.…”
Section: Methodsmentioning
confidence: 99%
“…These cells were selected because it is known that they have many properties similar to primary microglia cultures, which was confirmed in a previous publication. 47,56 Seeing that dPGS was nontoxic in microglia at a concentration of 100 nM (MTT assay, trypan blue exclusion assay and Hoechst 33342 labeling of cell nuclei, see below), we investigated if this lack of toxicity could be explained by their inability to enter the cells and only temporarily bind to plasma membrane putative selectin receptors. 20,53 For this we used dPGS-Cy5 and the control triglycerol-Cy5 (TG-Cy5) and untreated cells (controls for autofluorescence).…”
Section: ■ Introductionmentioning
confidence: 99%